2014
DOI: 10.1373/clinchem.2014.225565
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of Appendiceal Epithelial Tumors Using Massively Parallel Sequencing to Identify Somatic Mutations

Abstract: BACKGROUND Some epithelial neoplasms of the appendix, including low-grade appendiceal mucinous neoplasm and adenocarcinoma, can result in pseudomyxoma peritonei (PMP). Little is known about the mutational spectra of these tumor types and whether mutations may be of clinical significance with respect to therapeutic selection. In this study, we identified somatic mutations using the Ion Torrent AmpliSeq Cancer Hotspot Panel v2. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
77
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 18 publications
12
77
1
2
Order By: Relevance
“…Molecular profiling has been used effectively in other cancers to identify novel treatment options. Only two studies to date have reviewed the molecular profile of appendiceal cancers; those studies had very few patients (n=38 and 149) (18,19), and the analysis was limited to gene mutations. Our analysis encompassed multiple profiling platforms from gene alterations to gene amplification and protein expression levels, and 588 patients were evaluated, almost four times more than the previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular profiling has been used effectively in other cancers to identify novel treatment options. Only two studies to date have reviewed the molecular profile of appendiceal cancers; those studies had very few patients (n=38 and 149) (18,19), and the analysis was limited to gene mutations. Our analysis encompassed multiple profiling platforms from gene alterations to gene amplification and protein expression levels, and 588 patients were evaluated, almost four times more than the previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…20 Prevalence of KRAS & GNAS mutations in LAMN and PMP tumor samples has been reported in various studies with high variability ranging from 53-100% & 40-63% respectively (Table 1). [21][22][23][24][25][26] Differences in cell enrichment methods, genomic sequencing techniques, regional variation and small number patients in most of these studies may have contributed to this variation. Alakus et al reported KRAS and GNAS mutations in 10/10 and 9/10 tumor samples respectively, which is quite higher than previous studies.…”
Section: Pseudomyxoma Peritonei Genomicsmentioning
confidence: 99%
“…These tumors typically have different molecular pathways to carcinogenesis and do not have KRAS or GNAS mutations. 25 Given that KRAS mutations are associated with lack of response to anti-epidermal growth factor receptor (anti-EGFR) monoclonal antibodies (Cetuximab, Panitumumab), its absence in appendiceal adenocarcinomas with goblet cell features may allow for targeted anti-EGFR therapy. 32 …”
Section: Pseudomyxoma Peritonei Genomicsmentioning
confidence: 99%
“…Le gène GNAS code pour la sous-unité ␣ de la stimulatory guanine nucleotide-binding protein, qui régule l'adénylate cyclase des récepteurs couplés aux protéines-G. Des mutations somatiques activatrices de GNAS sont présentes dans diverses néoplasies et ont été récemment rapportées dans des LAMN et des PP [15,16]. En utilisant une technique moléculaire à haut débit (Next Generation Sequencing), Sio a montré que 24 % des PP présentent des mutations de GNAS [17].…”
Section: Marqueurs Moléculaires Des Ppunclassified